1989
DOI: 10.1042/bj2590921
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of hypoglycaemic action of methylenecyclopropylglycine

Abstract: The effects of methylenecyclopropylglycine (MCPG), the lower homologue of hypoglycin A, on starved rats are described. Upon oral ingestion of MCPG (43 mg/kg), a 50% decrease in blood glucose compared with controls was observed after 4 h. The plasma concentrations of lactate and non-esterified fatty acids were substantially increased during this period. The activity of general acyl-CoA dehydrogenase from isolated rat liver mitochondria was not significantly changed. By contrast, the activity of 2-methyl-(branch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
50
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(55 citation statements)
references
References 22 publications
5
50
0
Order By: Relevance
“…Consequently, cells can no longer use lipids as an energy source, and a profound hypoglycemia results. [16,17] In the chemical structures of 1 and 2 there is a d-unsaturated bond, which is similar to hypoglycin. Further investigations are needed to determine if 1 and 2 have this specific or a similar biochemical effect.…”
mentioning
confidence: 95%
“…Consequently, cells can no longer use lipids as an energy source, and a profound hypoglycemia results. [16,17] In the chemical structures of 1 and 2 there is a d-unsaturated bond, which is similar to hypoglycin. Further investigations are needed to determine if 1 and 2 have this specific or a similar biochemical effect.…”
mentioning
confidence: 95%
“…34–35 Both hypoglycin A and MCPG are documented compounds that can induce encephalopathy and hypoglycemia in animal studies. 8–12,22,26 …”
Section: Introductionmentioning
confidence: 99%
“…MCPA‐CoA, a ‘suicide’ or mechanism‐based inhibitor [7], causes irreversible inhibition through covalent modification of the flavin prosthetic group [7, 13]. The lower homologue, methylenecyclopropyl formyl‐CoA (MCPF‐CoA), exhibits a rather different target specificity, giving potent inhibition of 2MeBCD and IVD whilst SCAD is rather weakly inhibited and MCAD and LCAD are unaffected [14, 15]. Inhibition by this compound is irreversible but the mechanism of action is unknown [14, 15].…”
Section: Introductionmentioning
confidence: 99%
“…The lower homologue, methylenecyclopropyl formyl‐CoA (MCPF‐CoA), exhibits a rather different target specificity, giving potent inhibition of 2MeBCD and IVD whilst SCAD is rather weakly inhibited and MCAD and LCAD are unaffected [14, 15]. Inhibition by this compound is irreversible but the mechanism of action is unknown [14, 15]. Recently it was reported that spiropentane acetyl‐CoA (SPA‐CoA) preferentially inhibited octanoyl‐CoA dehydrogenase activity in liver homogenates [16].…”
Section: Introductionmentioning
confidence: 99%